MODEL KOLABORASI PENCEGAHAN PERNIKAHAN DINI BERBASIS COMMUNITY-BASED RESEARCH DI DESA PAGUNG KEDIRI - Karisma Dewi Puspasari (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2026)
This community service program aims to prevent child marriage through a Community-Based Research (CBR) approach that emphasizes active community participation in formulating needs-based solutions. The intervention was implemented over eight weeks through social mapping, the development of BERSAMA educational modules, training for adolescents and peer educators, an educational media campaign, and participatory evaluation. Descriptive statistical analysis showed that in the initial phase, most adolescents had low to moderate knowledge regarding reproductive health, psychological readiness, and religious understanding of marriage. After the intervention, adolescents' knowledge levels improved, as evidenced by a decrease in the number of adolescents with low knowledge and an increase in the number of adolescents with moderate and high knowledge. In addition to these quantitative achievements, the CBR approach strengthened community capacity through the formation of a shared understanding among adolescents, families, religious leaders, and village stakeholders regarding the importance of psychological, social, and spiritual readiness before marriage. This service program not only increased individual awareness but also contributed to the formation of a conceptual framework for adolescent policies and services at the village level.